Comment on "Historical Lynchings and the Contemporary Voting Behavior of Blacks" - Joanne Haddad; Lamis Kattan; Timo Wochner (Institute for Replication (I4R), 2023)
Williams (2022) ties the political participation of Blacks to historical lynchings that occurred in the United States. Her findings document lower Black voter registration rates in southern counties with greater number of historical lynchings. We show that this effect is driven by four outlier counties with relatively high Black lynching rates. Excluding these counties from the analysis yields a point estimate that is no longer statistically significant. Dropping the ninety-fifth percentile lynching rates and correcting the errors in voter registration rates rule out the effect size reported by Williams (2022), which now becomes close to zero and statistically insignificant. We also show that the main results are highly sensitive to the way lynching and voter registration rates are measured.
Keywords: D72; J15; N31; N32; N41; N42; Z13; 330